Relationship between lipid profile and B‑type natriuretic peptide T‑381C (rs198389) gene polymorphism in patients with stable coronary artery disease: Relationship between lipid profile and B‑type natriuretic peptide T‑381C - Ahmed Shekha, Gawhar; Asaaf Maulood, Kalthum; Sabir Shekha , Mudhir (Cellular and Molecular Biology, 2023)
The research explored the link between Brain Natriuretic Peptides (BNP) gene promoter T-381C polymorphism, serum BNP, and lipid profiles in Kurdish people from Iraq with stable coronary artery disease (CAD). The study was conducted on 62 individuals with CAD and 31 without CAD (control group). DNA was extracted from each individual’s sample using the Sanger sequencing method to study the BNP gene’s polymorphism. The identified alleles were TT, TC, and CC. The frequency of the TT genotype decreased significantly among the patient group compared to the control group, while the CC genotype’s frequency was higher (p<0.05). However, there was no significant increase in BNP levels in TC and CC genotypes compared to the TT genotype. Lipid profile values were not significantly different among the genotypes. The study utilized a cut-off value for BNP activity for predicting CAD and found that individuals with a BNP activity value less than the cut-off had significantly greater changes in lipid profile and renal function (p<0.05). Stepwise multivariate regression analysis showed that cholesterol was not the only primary determinant of BNP rate in subjects with stable CAD; oxidized low-density lipoprotein (Ox-LDL), a history of heart attacks, and oxidative stress malondialdehyde (MDA) had a significant effect. Homozygous C allele carriers at position 381 of the BNP precursors gene promoter were more likely to exhibit atherosclerosis lesions. We found that BNP rs198389 was not correlated with lipid profile and kidney disease.